2006
DOI: 10.1136/bjo.2005.072751
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal glaucoma screening for siblings of patients with primary open angle glaucoma: the Nottingham Family Glaucoma Screening Study

Abstract: Aims: To assess the prevalence and cumulative incidence of open angle glaucoma (OAG) in a cohort group of siblings of OAG probands. Methods: Between 1994 and 2003, a group of siblings of OAG probands underwent both initial and follow up standardised ophthalmic examinations. Siblings were classified as ''definite glaucoma'' (primary OAG (POAG) and normal tension glaucoma (NTG)), ''glaucoma suspects'' (NTG suspects or ocular hypertension (OHT)), and normal. The prevalence and cumulative incidence of OAG over the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
26
2

Year Published

2009
2009
2025
2025

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 23 publications
0
26
2
Order By: Relevance
“…Further investigation is required to verify our results prior to interpreting the association of nationality to glaucoma. Racial differences are observed in glaucoma and familial as well as genetic etiologies have been proposed for different types of glaucoma 3132. A high consanguinity rate in the Qatari population may be a factor in this higher prevalence of glaucoma 33…”
Section: Discussionmentioning
confidence: 99%
“…Further investigation is required to verify our results prior to interpreting the association of nationality to glaucoma. Racial differences are observed in glaucoma and familial as well as genetic etiologies have been proposed for different types of glaucoma 3132. A high consanguinity rate in the Qatari population may be a factor in this higher prevalence of glaucoma 33…”
Section: Discussionmentioning
confidence: 99%
“…Photographic evidence of NFL defect 1 and evidence of disc rim defect 12 have also been recognized as risk factors for VF loss. 13,14 In a recent meta-analysis, 15 Ernest et al identified a list of recognized baseline prognostic factors for future VF loss, including disc hemorrhage (for normal tension glaucoma), VF loss, IOP and exfoliation syndrome, while a definitive association was not proven for other factors, such as family history. However, none of these risk factors by themselves are reliable predictors of glaucoma progression, and clinicians must consider all of them in glaucoma patient management.…”
Section: Introductionmentioning
confidence: 99%
“…A family history of glaucoma is a major risk factor for POAG, and the prevalence of POAG in first-degree relatives of affected patients is between 4 and 10 times that of the general population (47). The higher concordance of glaucoma among monozygotic twins compared to dizygotic twins is also consistent with a significant genetic predisposition (8, 9).…”
Section: Introductionmentioning
confidence: 99%